Prevalence of migraine in low-tension glaucoma and primary open-angle glaucoma in Japanese. Issue 4 (April 1991) - Usui, T; Iwata, K; Shirakashi, M; Abe, H
Abstract : We studied the prevalence of migraine in low-tension glaucoma (LTG) and primary open-angle glaucoma (POAG). Seventy seven Japanese patients with LTG, 73 with POAG, and 75 normal subjects were randomly selected and tested with a headache questionnaire. The prevalence of headache with or without typical migrainous features (unilateral headache or ocular pain, nausea, vomiting, and visual disturbance before headache) was 51% in LTG, 42% in POAG, and 44% in normal patients. The prevalence of headache with two migrainous features or more (probable migraine) was 17% in LTG, 11% in POAG, and 12% in normal subjects. The prevalence of headache with three migrainous features (classical migraine) was 5% in LTG, 3% in POAG, and 3% in normal subjects. There was no statistically significant difference in the prevalence of any types of migraine between the three groups of patients (p greater than 0.05). These results suggest there is no significant relationship between migraine and LTG or POAG in Japanese patients.